Kualitas Air Daerah Aliran Sungai Dendeng dan Pemanfaatan Data Bagi Manajemen Lingkungan - Vebronia M D Solo (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2020)
The water quality monitoring program (WQM) of Dendeng watershed plays an essential role in supporting water quality management and pollution control in Kupang Municipality. This requires an optimal WQM framework. Therefore, this study aimed at evaluating the effectivity of WQM at Dendeng watershed by: (1) assessing its water quality as well as its spatial and temporal variabilities, (2) identifying technical and management challenges in the current WQM as well as its implication on formulating environmental management and policy. For the purposes, WQM data Dendeng watershed between 2018 and 2019 was statistically analysed by performing two-way Anova and Cluster analysis. Next, a SWOT (Strenghts, Weaknesses, Opportunities, and Threats) was implemented by an interview and assessing documents related the existing WQM in Kupang. Results showed that pH, TDS, and COD still met national standard of water quality, while DO, E.coli, and total coliform in several sampling points and monitoring times did not reveal the same result. The water quality in upstream and downstream were different significantly. The water quality was considerably poor in September and November. Nonetheless, the WQM data has not been adequately comprehensive in fulfilling data requirements for environmental management and policy in Kupang Municipality. Thus, the Kupang Municipal Government needs an optimization of its existing WQM.